2015
DOI: 10.1371/journal.pone.0133880
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of a Biomimetic Pericyte-Covered 3D Microvascular Network

Abstract: Pericytes enveloping the endothelium play an important role in the physiology and pathology of microvessels, especially in vessel maturation and stabilization. However, our understanding of fundamental pericyte biology is limited by the lack of a robust in vitro model system that allows researchers to evaluate the interactions among multiple cell types in perfusable blood vessels. The present work describes a microfluidic platform that can be used to investigate interactions between pericytes and endothelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
131
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(140 citation statements)
references
References 42 publications
(54 reference statements)
9
131
0
Order By: Relevance
“…Representative data from multiple experiments show drastic differences in vascular area, branch geometry, and overall network connectivity between HPP and HLF cocultures, as observed daily by confocal microscopy. [25,29] We postulated that differences between stromal cell interactions and vascular growth could be due to cell specific differences in cytokine expression. Similar decreases in vessel density and diameter have been shown with HUVEC-pericyte cultures in 3D angiogenesis assays.…”
Section: Placental Pericytes Inhibit Microvascular Growthmentioning
confidence: 99%
“…Representative data from multiple experiments show drastic differences in vascular area, branch geometry, and overall network connectivity between HPP and HLF cocultures, as observed daily by confocal microscopy. [25,29] We postulated that differences between stromal cell interactions and vascular growth could be due to cell specific differences in cytokine expression. Similar decreases in vessel density and diameter have been shown with HUVEC-pericyte cultures in 3D angiogenesis assays.…”
Section: Placental Pericytes Inhibit Microvascular Growthmentioning
confidence: 99%
“…Proliferating ECs in the surrounding matrix form new sprouts, and these sprouts make loops to become a vascular lumen [23]. There have been on-a-chip models that recapitulate hallmarks of the angiogenesis, such as vascular sprouting [18 •• ,24], network formation [20,21], perfused lumen formation [18 •• ,19,21], and maturation [25,26]. For example, Nguyen et al .…”
Section: Models For Tumor Angiogenesismentioning
confidence: 99%
“…Another recent paper by Kim et al . employed human placental pericytes, and showed pericyte coverage on their 3D microvascular network [26]. …”
Section: Models For Tumor Angiogenesismentioning
confidence: 99%
“…Interestingly, the ratio of ECs to PCs varies from 1:1 in neural tissue to 10:1 in skeletal muscle, which makes PCs attractive for investigation in the field of tissue engineering. 15 An isolated model for investigating the specific interaction between ECs and PCs has been demonstrated using a threedimensional microfluidic system by Kim et al 16 Compared with monoculture of ECs, coculture of PCs and ECs showed an increased number of junctions and branches, reduced diameter, and decreased permeability. Defined coculture and microfluidic model system of ECs, and PCs may be employed further to effectively screen PC-specific drugs for their effect on various biochemical factors.…”
Section: Interaction Between Pcs and Ecsmentioning
confidence: 99%